Novel point mutation and intronic mutations of RB1 gene in retinoblastoma patients in Indonesia (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Retinoblastoma (RB) is an inherited disorder caused by the RB1 gene mutation in retinal cells or germline mutation. Identifying the specific mutation is crucial for prognosis, inheritance risk assessment, and treatment planning. This study aimed to identify the germline mutation in the RB1 gene in patients with RB and their parents from the eastern part of Indonesia. METHODS This observational analytic study recruited patients with RB and their parents between 2016 and 2018 at Dr. Wahidin Sudirohusodo Hospital, Makassar, Indonesia. The normal control subjects were children from the outpatient clinic at the Department of Ophthalmology, Universitas Hasanuddin Hospital. Ophthalmic examinations and peripheral blood tests were performed in RB patients, their parents, and control subjects. Genomic DNA was isolated from blood leukocytes and amplified using conventional PCR. Hotspot exons 8, 10, 14, 17, and 22 were screened for mutations using the Sanger method. RESULTS There were 21 patients with RB (16 unilateral and 5 bilateral) and 14 normal subjects. Of the 184 variations detected in RB patients, 164 were also found in normal subjects. 19 intronic mutations in introns 10, 16, 17, and 21, and 1 novel missense mutation in exon 17 were identified. Parental testing revealed 8 substitutions in exon 17 and 5 intronic mutations in introns 16 and 17 of the parents. None of the variations in exons were passed to their children. CONCLUSIONS This study found a novel missense mutation in exon 17 of the RB1 gene.